2023
DOI: 10.1021/acsomega.3c00352
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Spectroscopic Properties of the Alkaline-Earth-Metal Monohydrides toward Laser Cooling and Magneto-Optical Trapping

Abstract: Alkaline-earth-metal monohydrides MH (M = Be, Mg, Ca, Sr, Ba) have long been regarded as promising candidates toward laser cooling and trapping; however, their rich internal level structures that are amenable to magneto-optical trapping have not been completely explored. Here, we first systematically evaluated Franck−Condon factors of these alkaline-earth-metal monohydrides in the A 2 Π 1/2 ← X 2 Σ + transition, exploiting three respective methods (the Morse potential, the closed-form approximation, and the Ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Thus, it was indicated that for a given number of nitrogen donor sites in Ga 5 N 10 _NC, the stabilities of M 2+ are higher than M + complexes as Ca 2+ @ Ga 5 N 10 _NC > Mg 2+ @ Ga 5 N 10 _NC > Be 2+ @ Ga 5 N 10 _NC >> K + @ Ga 5 N 10 _NC > Na + @ Ga 5 N 10 _NC > Li + @ Ga 5 N 10 _NC. Moreover, it is proposed that alkali/alkaline earth-metal-adsorbed can be used to decorate and enlarge the optoelectronic properties of Ga 5 N 10 _NC, which can be used to produce photoelectric devices [53].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was indicated that for a given number of nitrogen donor sites in Ga 5 N 10 _NC, the stabilities of M 2+ are higher than M + complexes as Ca 2+ @ Ga 5 N 10 _NC > Mg 2+ @ Ga 5 N 10 _NC > Be 2+ @ Ga 5 N 10 _NC >> K + @ Ga 5 N 10 _NC > Na + @ Ga 5 N 10 _NC > Li + @ Ga 5 N 10 _NC. Moreover, it is proposed that alkali/alkaline earth-metal-adsorbed can be used to decorate and enlarge the optoelectronic properties of Ga 5 N 10 _NC, which can be used to produce photoelectric devices [53].…”
Section: Discussionmentioning
confidence: 99%